Outcomes for End-of-Life Patients With Anticipatory Grieving: Insights From Practice With Standardized Nursing Terminologies Within an Interoperable Internet-Based Electronic Health Record. Issue 3 (June 2017) - Johnson, Julie; Lodhi, Muhammad Kamran; Cheema, Umer; Stifter, Janet; Dunn-Lopez, Karen; Yao, Yingwei; Johnson, Andrew; Keenan, Gail M.; Ansari, Rashid; Khokhar, Ashfaq; Wilkie, Diana J.
Abstract : Anticipatory grieving, grief associated with an impending loss, is common for patients facing end of life or for their families. There is little research on the outcomes of interventions for anticipatory grieving among hospitalized patients. A descriptive, comparative analysis of an existing valid and reliable data set that was obtained through routine nursing clinical practice using standardized nursing terminologies was completed. We applied data mining techniques on a targeted data set consisting of hospital episodes for end-of-life patients who were given a diagnosis of anticipatory grieving. Less than 50% of the patients given a diagnosis of anticipatory grieving met the expected ratings of monitored nursing outcomes at the time of death or discharge. Specifically, for the spiritual health outcome, only more than 50% of the patients met the expected outcome rating. For the comfortable death outcome, only 45.9% of the patients met the outcome rating. For the comfortable death outcome, patients were significantly more likely not to meet the expected outcome rating if they were also given a diagnosis belonging to the physical comfort class (χ 2 (1) = 8.99, P < .003). These results demonstrate that expected outcomes are not being met and suggest the need of better education for the clinicians about the diagnosis and treatment of anticipatory grieving.